Advanced optic-fiber sensor for progesterone concentration detection relying on the temperature-compensated reflective structure functionalized with molecularly imprinted polymer - Hanlin Liu; Miao Liu; Shuyuan Guo; Jingru Mao; Yongfeng Zou; Yuejiang Yu; Dandan Sun; Jie Ma (Food Chemistry: X, 2025)
A cascaded optic-reflector sensing system combining a microfiber interferometer (MFI) and a gold-coated tilted fiber Bragg grating (TFBG) is proposed for detecting progesterone (PG) concentration. The sensor uses molecularly imprinted polymers (MIP) as a recognition layer and metal-organic frameworks (MOFs) for enhanced sensitivity. The remove and rebind of PG will both cause changes in the local refractive index (RI) on MFI, and these changes can be monitored by the intensity variations on TFBG. Experimental results show a detection range of 10−6–20 μg/ml, with a sensitivity of 41,837 dB/(μg/ml) and a limit of detection (LOD) of 10−6 μg/ml. Simultaneously, it has been established that the sensor has good specificity in ten different real samples. This cascaded structure reflective sensor provides a simple and reliable technology for the quantitative detection of PG concentration in dairy products and water.